2014
DOI: 10.1037/ort0000036
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for understanding the association between school bullying victimization and substance misuse.

Abstract: This article reviews current research findings and presents a conceptual framework for better understanding the relationship between bullying victimization (hereafter referred to as victimization) and substance misuse (hereafter referred to as SM) among adolescents. Although victimization and SM may appear to be separate problems, research suggests an intriguing relationship between the two. We present a brief, empirical overview of the direct association between victimization and adolescent SM, followed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 120 publications
(197 reference statements)
10
90
0
Order By: Relevance
“…In contrast, other research indicates bullies are more likely than bully-victims to engage in excessive drinking and other substances (Kaltiala-Heino et al, 2000). Furthermore, bullying victimization can pose risk for substance use directly (Radliff et al, 2013) or indirectly through its direct influence on internalizing problems (Hong, Davis, Sterzing, Yoon, Choi, & Smith, 2014). Prospective studies have found early involvement in bullying is linked to subsequent substance use as an adult (Min, Catalano, Haggerty, & Abbot, 2011; Niemela et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other research indicates bullies are more likely than bully-victims to engage in excessive drinking and other substances (Kaltiala-Heino et al, 2000). Furthermore, bullying victimization can pose risk for substance use directly (Radliff et al, 2013) or indirectly through its direct influence on internalizing problems (Hong, Davis, Sterzing, Yoon, Choi, & Smith, 2014). Prospective studies have found early involvement in bullying is linked to subsequent substance use as an adult (Min, Catalano, Haggerty, & Abbot, 2011; Niemela et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have found early involvement in bullying is linked to subsequent substance use as an adult (Min, Catalano, Haggerty, & Abbot, 2011; Niemela et al, 2011). Although the available research characterizes the linkages between bullying and substance use, less research has consistently offered a comparative perspective of risk based on status as a bully, victim, and bully-victim (Hong et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although these processes are understudied among youth, evidence suggests that internalizing problems, characterized by inhibition and negative mood states, plays a role in associations between peer victimization and substance use. 7,13,14 In particular, peer victimization may promote depressive symptoms, 15 -18 which, in turn, may lead to greater youth substance use. 19,20 Youth are typically at greatest risk of peer victimization during late childhood and early adolescence, with rates of victimization decreasing through the remainder of adolescence.…”
mentioning
confidence: 99%
“…We therefore tested a longitudinal mediational model to determine whether peer victimization in the fifth grade is associated with a greater likelihood of substance use in the tenth grade via the mediator of depressive symptoms in the seventh grade. Given previous research on gender differences in peer victimization and substance use, 7 we further explored whether the model differed between boys and girls. A better understanding of the long-term implications of peer victimization on substance use, as well as the role of depressive symptoms in these associations, may inform pediatricians' efforts to address substance use among youth.…”
mentioning
confidence: 99%
“…For example, victims of bullying were more likely to have a higher risk of depression, suicidal ideation, anxiety, sleep disturbances, social isolation and feelings of loneliness (11)(12)(13)(14). Moreover, the prevalence of substance use including alcohol, nicotine and inhalants was reportedly higher among victims of bullying than non-victims (12, 15,16). The perpetration of bullying is also associated with externalizing symptoms such as aggression, truancy and delinquency (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%